ChemInform Abstract: Highly Enantioselective Construction of Tertiary Thioethers and Alcohols via Phosphine‐Catalyzed Asymmetric γ‐Addition Reactions of 5H‐Thiazol‐4‐ones and 5H‐Oxazol‐4‐ones: Scope and Mechanistic Understandings. Issue 50 (December 2015) - Wang, Tianli; Yu, Zhaoyuan; Hoon, Ding Long; Huang, Kuo‐Wei; Lan, Yu; Lu, Yixin
Abstract: For the first time, amino‐acid derived bifunctional phosphines are used as catalysts to synthesize a wide range of substituted thiazolone and oxazolone derivatives.